Refleksi Isu Sosial Di Jepang Dalam Empat Karya Fiksi: Hiyama Kentarou No Ninshin, Sanju Mariko, Sensei No Kaban, Dan Death Sweeper - Budi Mulyadi; Yusifa Tamarlin Margie; Umar Bayu Wisesa (Diponegoro University, 2021)
This study examines how Japanese social issues are portrayed in four fiction works in the form of manga and novels:”Hiyama Kentarou no Ninshin”,”Sanju Mariko”, “Sensei no Kaban”, and “Death Sweeper”. Using qualitative methods by conducting descriptive analysis method to describe how social ties and community weakening in Japan in the scope of Shoushikoureika and Kodoku issues are portrayed in the said works. The findings of this study are the followings: 1) Hiyama Kentarou no Ninshin portrayed the dilemma faced by women and men in child-bearing and child-rearing activities. 2) Sanju Mariko portrayed the vigor of Japanese elders and their struggle to find a place in society. 3) Sensei no Kaban portrayed the changes of Japanese narrowing social structure. 4) Death sweeper portrayed lonely death as the effect of Kodoku. As a reflection of reality, fiction works could also serve as a cross-cultural study by examining the phenomenon explained inside the works through the eyes of the writers and characters.